Constructing hierarchical carbon framework and quantifying water transfer for novel solar evaporation configuration. (December 2019) - Geng, Yang; Zhang, Kezhen; Yang, Ke; Ying, Peijin; Hu, Lijun; Ding, Jun; Xue, Junmin; Sun, Wan; Sun, Kuan; Li, Meng
Abstract: Solar interfacial thermal evaporation system has recently drawn extensive attention because it enables low heat loss and high solar thermal conversion efficiency for water desalination and sewage treatment. However, the portability and low cost of solar thermal material are still challenges for its further practical implementation. Besides, the fundamental understanding of thermal management on the effect of efficiency remains unclear. Herein, we demonstrate a novel strategy to construct a solar thermal material of hierarchical carbon framework decorated by Fe3 O4 nanoparticles (Fe3 O4 @CA/CF). Under 1 sun irradiation (1 kW m −2 ), the as-prepared absorber shows a broad spectrum absorption (∼99%) and outstanding water evaporation rate (1.316 kg m −2 h −1 ) with ∼91.0% efficiency, which is six times as that of water without absorber. Significantly, a marvelous volumetric water evaporation rate (up to 658 kg m −3 h −1 ) has been obtained, indicating its portable and cost-effective superiorities. Besides, for the first time, we quantitatively reveal a strong correlation between evaporation efficiency and porosity of 1D water path in isolation configuration through numerical simulation; the optimum range of porosity for evaporation is also identified. Combining low-cost materials, broad spectrum absorption, high solar thermal conversion efficiency and excellent portability, the as-prepared material is likely to be a promising absorber for solar interfacial evaporation system. Graphical abstract: Image 1